1988
DOI: 10.1136/adc.63.9.1016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentations of Ehlers Danlos syndrome type IV.

Abstract: Ehlers Danlos syndrome type IV is an often lethal disease caused by various mutations of type III collagen genes. It presents in infancy and childhood in several ways, and the symptoms and signs include low birth weight, prematurity, congenital dislocation of the hips, easy inappropriate bruising (sometimes suspected as child battering), and a diagnostic facial phenotype. These features predict a lethal adult disease often complicated by fatal arterial rupture in early or middle adult life. Most affected patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…Patients with EDS have been reported to suffer from rectal prolapse from early childhood to the sixth decade [37,16]. Surgical treatment of rectal prolapse has been reported to be associated with risk of complications, which is why some authors recommend careful consideration in planning the surgical treatment [38,18]. Because of the risk of chronic constipation [35], it is suggested that patients with EDS maintain a regular laxative regime in order to try to avoid rectal prolapse [18].…”
Section: Colonmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with EDS have been reported to suffer from rectal prolapse from early childhood to the sixth decade [37,16]. Surgical treatment of rectal prolapse has been reported to be associated with risk of complications, which is why some authors recommend careful consideration in planning the surgical treatment [38,18]. Because of the risk of chronic constipation [35], it is suggested that patients with EDS maintain a regular laxative regime in order to try to avoid rectal prolapse [18].…”
Section: Colonmentioning
confidence: 99%
“…Rectum Data regarding rectal diseases in patients with EDS are based on a single clinical study [16] and on case report data [37,38]. Patients with EDS have been reported to suffer from rectal prolapse from early childhood to the sixth decade [37,16].…”
Section: Colonmentioning
confidence: 99%
“…3 The hallmarks of the disease, however, are severe surgical complications, some of which are frequently fatal, and account for the reduced life expectancy of these patients, resulting in a mean age at death of 35 to 40 years. 7,8 These are spontaneous ruptures of aneurysms, arteriovenous fistulas or large-size arteries 14 (as occurred in our patient). Splenic rupture has also been reported.…”
Section: Barabasmentioning
confidence: 99%
“…Joint dislocations and severe bruising with thin skin and capillary prominence or telangiectasia are common. 8 They include typical facial features (i.e., a thin, pinched nose and large eyes with a startling and prominent appearance, because of paucity of adipose tissue) and acrogeria (defining hands with fine fingers and covered by thin and wrinkled skin, which looks prematurely aged). 7 The association of both club foot and spontaneous penumothorax with this syndrome has also been noted.…”
Section: Barabasmentioning
confidence: 99%
“…However, phenotypic features of EDS IV may not always be particularly evident. A typical facial appear ance, with thin nose and lips, large and expressive eyes, lobeless ears [4][5][6] and a prematurely aged appearance (acrogeric form of EDS IV), is a feature of some patients, although others may not show skin involvement or such facial features. We describe a sporadic case of EDS IV occurring in a woman who presented with a spontaneous carotid-caver nous fistula (CCF) that was successfully treated endovascularlv, with long-term relief.…”
Section: Introductionmentioning
confidence: 99%